PENGARUH PENDAPATAN ORANG TUA TERHADAP MINAT SISWA KELAS XII MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI DI SMKN 2 PARIAMAN - Rizky, Thesa Permata; Eddison, Ahmad; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by not many students of SMKN 2 Pariaman who entered college in previous years and it is not yet known the cause of the problem whether it is influenced by parental income or there are other influences that cause students of SMKN 2 Pariaman not to continue their education to college. The problem formulation in this study is how the interest of students of SMKN 2 Pariaman to continue their education to college and how the influence of parental income on the interests of grade XII students continue their education to college at SMKN 2 Pariaman. The purpose of this study was to find out how the interest of students of SMKN 2 Pariaman to continue their education to college and to find out how the influence of parental income on the interests of grade XII students continued their education to college at SMKN 2 Pariaman. This research method is Quantitative with data collection instruments used, namely questionnaires consisting of 24 questions and 4 indicators. The population in this study was students of grade XII SMK Negeri 2 Pariaman, with a sample of 68 respondents. Data analysis techniques in this study used Linear Regression Analysis with SPSS version 26. Based on the results of the research conducted, the interest of grade XII students to continue their education to college is in a very high category. This is because the result of the largest frequency is at very high intervals of 69%, and there is no significant influence between the income of parents and the interest of grade XII students to continue their education to college. This is evidenced from the results of the F test obtained Fhitung of 1,013 and Ftabel of (3.98), where it shows that Fhitung < Ftabel, so that Ho was accepted and Ha rejected. So that there is no influence of parental income on the interest of grade XII students to continue their education to college.So the hypothesis in this study was rejected and the influence of parental income on students' interest in college admission was very low. Because based on the results of the calculation above is known coefficient determination (R square) of 0.015, which contains the understanding that the influence of free variables (parental income) on bound variables (interest in entering college) is 1.5%. This means that the significant contribution between parents' income to the interest of students continuing education to college is 1.5%. Thus, it can be concluded that the interest of grade XII students of SMKN 2 Pariaman to continue their education to college is in a very high category and there is no influence of parental income on the interest of grade XII students of SMKN 2 Pariaman continuing their education to college.Key Words: Effect, Income, Parents, Interest, College